1965
DOI: 10.1063/1.1696778
|View full text |Cite
|
Sign up to set email alerts
|

One-Dimensional Model of Polymer Adsorption

Abstract: A detailed treatment of the conformations of a one-dimensional polymer molecule adsorbed to a surface is given. The average number of contacts of the chain with the surface, the end-to-end length, and the distribution of segments ρ(z) with respect to distance z from the surface are computed as functions of the chain length (N) of the polymer and the attractive energy of the surface. Both theoretical and Monte Carlo calculations are used. A transition is found at an attractive energy of kT ln 2. For attractive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

1980
1980
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(56 citation statements)
references
References 8 publications
3
53
0
Order By: Relevance
“…The theoretical description of polymer adsorption at surfaces is in terms of structures having "trains" of sequential segments adsorbed to the surface, "loops" of desorbed segments between the trains, and desorbed "tails" at either end. Early descriptions based on random walks and Monte Carlo simulations modeled the case of the isolated chain at a surface [13,14]. These showed that the fraction of adsorbed segments for a polymer of length n is proportional to n 1͞2 for critical values of the segmentsurface interaction energy that are of order k B T .…”
Section: Figmentioning
confidence: 99%
“…The theoretical description of polymer adsorption at surfaces is in terms of structures having "trains" of sequential segments adsorbed to the surface, "loops" of desorbed segments between the trains, and desorbed "tails" at either end. Early descriptions based on random walks and Monte Carlo simulations modeled the case of the isolated chain at a surface [13,14]. These showed that the fraction of adsorbed segments for a polymer of length n is proportional to n 1͞2 for critical values of the segmentsurface interaction energy that are of order k B T .…”
Section: Figmentioning
confidence: 99%
“…[6] It is well known that the introduction of a boundary can alter the physical character of a statistical system. [7] As an example of the subtle effects that our method reveals for statistical systems near curved boundaries, we discuss the adsorption-desorption transition of polymers growing near an attractive boundary. [8] In the limit of an infinitely extended polymer, a finite fraction P (κ) of monomers gets adsorbed on the boundary as soon as the attractive potential κ on the boundary increases above a critical value.…”
mentioning
confidence: 99%
“…For example, an additional increase of the adsorbed macromolecule dimension was observed for PEO [2]. DiMarzio and McCrackin have shown [25] that for high-molecular polymers the mean squared dimension of a statistical chain, perpendicular to an interface, approaches an asymptotic value Adopted from our previous paper [2].…”
Section: Discussionmentioning
confidence: 92%